(3GdHWdGf GdLRFj ddYbhO hGdJUQaGJ GdbGfhfjI (B/s - (3eMeO MSf YhGO GdQLhHs; (3fRjg eMeO GdUGOb GdegOjs; (3LGeYI GdOhd GdYQHjIs (3eYgO GdHMhK hGdOQGSGJ GdYQHjIs ((3GdbGgQI (B:s (3eYgO GdHMhK hGdOQGSGJ GdYQHjI (B- (3LGeYI GdOhd GdYQHjI,s, 2002)
(3JHOC gPg GdQSGdI HaUd JegjOj Yf GdEfbGU heagheg, Ke JfbSe Edi HGHjf; MjK jJfGhd GdHGH GdChd GdWHjYI GdbGfhfjI ddEfbGU, hGdHGH GdKGfj jJfGhd fWGb GdEfbGU hJWHjbGJg(B.s
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdOhd GdYQHjI, eYgO GdHMhK hGdOQGSGJ GdYQHjI, bSe GdbGfhf GdeOfj (B2002.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 113-118 (3UaMIs
Keywords: (3GdbGfhf GdeOfjs; (3GdHWdGf GdLRFjs; (3GdJUQaGJ GdbGfhfjIs; (3GdEfbGU hELGRI GdYbOs; (3TQhW JMhd GdYbOs; (3TQhW EYeGd GdEfbGUs; (3EfbGU eOI GdGJaGbs; (3EfbGU GdCLQIs; (3GdEfbGU ddJOdjSs; (3QSGFd LGeYjIs -- (3LGeYI GdOhd GdYQHjIs -- 2002.